A patient's dilemma : to litigate or otherwise - Ravichandran, N., (SAGE Business Cases., 2018)
The patient, a middle-aged woman was advised hysterectomy by an Oncology Gynaecology surgeon, based on the patient's health conditions, symptoms and clinical investigations. The patient however, decided to seek out a gynecologist for a second opinion on whether she should get a hysterectomy. The second consultation was far from a pleasant experience and it appeared as though the consultant was a leveraging an opportunity to maximize revenue. Students are asked to consider if legal action against the consultant gynecology would be fruitful in this instance.